A Mother Who Experienced TRALI After a Caesarian Section on the Indication of Severe Pre-eclampsia with a Macrosomic Fetus - Lestari, Puti Fajri; Satria, Pom Harry (Andalas Obstetrics And Gynecology Journal, 2025)
Introduction: Transfusion-Related Acute Lung Injury (TRALI) is a severe, often fatal, complication of blood transfusion. Obstetric patients with severe pre-eclampsia are uniquely susceptible due to a "two-hit" mechanism, where the underlying inflammatory condition primes the lungs for injury from a subsequent blood transfusion. This report presents a case of post-transfusion respiratory distress in such a high-risk patient, highlighting the diagnostic challenges. Case Report: A mother with severe pre-eclampsia underwent a caesarean section for a macrosomic fetus, complicated by postpartum hemorrhage. She was transfused with two units of Packed Red Cells (PRC). Approximately 12 hours after the transfusion was completed, she developed acute-onset, progressive shortness of breath, requiring management in the High Care Unit. Discussion: In this complex postpartum case, the central challenge is diagnosing acute respiratory distress following Caesarean delivery, severe pre-eclampsia, and a blood transfusion. Given the patient’s heightened vulnerability due to pre-eclampsia and surgery, the transfusion may have triggered acute lung injury via the "two-hit" model. TRALI diagnosis relies on clinical suspicion and requires immediate cessation of transfusion, respiratory support, and careful hemodynamic management. Conclusion: This case underscores the importance of recognizing TRALI as a potential cause of respiratory distress in obstetric patients with pre-eclampsia, emphasizing the need for prompt diagnosis and supportive care.